2008
DOI: 10.1007/s00542-008-0702-4
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation and analysis of electrically actuated microbeam-based MEMS capacitive switch

Abstract: The MEMS capacitive switch based on fixedfixed microbeam has garnered significant attention due to their geometric simplicity and broad applicability. The accurate model which describes the multiphysical coupledfield of MEMS capacitive switch should be developed to predict their electromechanical behaviors. The improved macromodel of the fixed-fixed microbeam-based MEMS capacitive switch is presented to investigate the behavior of electrically actuated MEMS capacitive switch in this paper, the macromodel provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…On the other hand, the tensile axial force has the effect to stretch the beam, which hinders the pull-in, so more voltage (larger electrostatic force) is required. Similar conclusions have also been found by the theoretical and experimental studies in the literature (AbdelRahman et al, 2002;Ballestra et al, 2010;He et al, 2009;Huang et al, 2001;Jia et al, 2011).…”
Section: Snap-through Behaviorsupporting
confidence: 86%
“…On the other hand, the tensile axial force has the effect to stretch the beam, which hinders the pull-in, so more voltage (larger electrostatic force) is required. Similar conclusions have also been found by the theoretical and experimental studies in the literature (AbdelRahman et al, 2002;Ballestra et al, 2010;He et al, 2009;Huang et al, 2001;Jia et al, 2011).…”
Section: Snap-through Behaviorsupporting
confidence: 86%
“…Actually, a fringing eld always exists, and a more realistic situation, including the \fringing-eld", should be taken into consideration. The electrostatic force per unit length can be written as follows [1,33]:…”
Section: Modeling and Formulationmentioning
confidence: 99%
“…Dynamic analysis on cantilever based sensors is also performed in [5,6], and they observed the behavior by changing the deposited mass on tip of cantilever, which showed that the shift in resonance frequency is directly related to the added mass. In [7], an improved model of micro bridge based MEMS switch was developed to account for large deflections and dynamic loads. They used this model to predict the behavioral dynamics of the switch under capacitive actuation.…”
Section: Introductionmentioning
confidence: 99%